Distribution, scarcity, and Merchant App MyPertamina implementation in LPG 3 Kg purchase decisions: An Islamic economics perspective - Nasution, Dita Aidila Syaharani; Ridwan, Muhammad; Batubara , Maryam (Universitas Islam Indonesia, 2026)
IntroductionIndonesia’s subsidized three-kilogram liquefied petroleum gas program is intended to protect household and microenterprise access to affordable energy, yet distribution irregularities, localized scarcity, price deviations, and uneven implementation of digital subsidy governance continue to challenge its effectiveness. These problems raise broader questions about how physical distribution and provider-operated digital systems create customer value and shape purchasing behavior in a regulated essential-energy market.ObjectivesThis study examines the relationships of distribution, scarcity, and consumer-perceived implementation of Merchant App MyPertamina with three-kilogram liquefied petroleum gas purchase decisions. It further investigates customer perceived value as an intervening mechanism linking these distributional and digital-governance conditions with purchasing behavior.MethodA quantitative explanatory cross-sectional design was employed using data from 205 three-kilogram liquefied petroleum gas users across all 23 districts of Langkat Regency, North Sumatra, Indonesia. Respondents were selected through purposive sampling, and data were collected from March to May 2026 using a five-point Likert-scale questionnaire. The measurement and structural models were evaluated using partial least squares structural equation modeling with SmartPLS 4.0.ResultsDistribution was positively associated with both customer perceived value and purchase decisions, while customer perceived value was positively associated with purchase decisions. Consumer-perceived implementation of Merchant App MyPertamina significantly improved customer perceived value but showed no significant direct relationship with purchase decisions. Scarcity did not significantly influence customer perceived value, and its indirect relationship with purchase decisions through customer perceived value was unsupported. Customer perceived value partially mediated the relationship between distribution and purchase decisions and fully mediated the relationship between Merchant App MyPertamina implementation and purchase decisions. The model explained 59.4% of the variance in purchase decisions and 51.5% of the variance in customer perceived value.ImplicationsThe findings indicate that reliable physical distribution and consumer-visible value creation are more important than digitalization alone in shaping subsidized energy purchasing behavior. Digital subsidy governance should therefore emphasize transparency, fairness, service clarity, and accountable targeting alongside reliable last-mile supply.Originality/NoveltyThis study integrates physical distribution, scarcity, provider-operated digital subsidy governance, customer perceived value, and purchase behavior within one model and identifies customer perceived value as the mechanism connecting distributional and digital-governance conditions with consumer behavior in a subsidized essential-energy market.